Identification of the new C*07:555 allele in an unrelated donor for HSCT. (1st February 2017) - Condello, R.; Battarra, M.; Testi, M.; Testa, G.; Andreani, M.
Abstract : HLA‐C*07:555 differs from C*07:01:01:01 by a C to G substitution in exon 2.